If a, b, c are all non zero and a+b+c =0. prove that a square \bc + b square \ca +c square \ab = 3.
Answers
Answered by
5
We know that if
![a + b + c = 0 a + b + c = 0](https://tex.z-dn.net/?f=a+%2B+b+%2B+c+%3D+0)
Then,
![a ^{3} + {b}^{3} + {c}^{3} = 3abc a ^{3} + {b}^{3} + {c}^{3} = 3abc](https://tex.z-dn.net/?f=a+%5E%7B3%7D+%2B+%7Bb%7D%5E%7B3%7D+%2B+%7Bc%7D%5E%7B3%7D+%3D+3abc)
Now, dividing both sides by abc, we get
![\frac{ {a}^{3} }{ abc} + \frac{ {b}^{3} }{abc} + \frac{ {c}^{3} }{abc} = \frac{3abc}{abc} \frac{ {a}^{3} }{ abc} + \frac{ {b}^{3} }{abc} + \frac{ {c}^{3} }{abc} = \frac{3abc}{abc}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Ba%7D%5E%7B3%7D+%7D%7B+abc%7D+%2B+%5Cfrac%7B+%7Bb%7D%5E%7B3%7D+%7D%7Babc%7D+%2B+%5Cfrac%7B+%7Bc%7D%5E%7B3%7D+%7D%7Babc%7D+%3D+%5Cfrac%7B3abc%7D%7Babc%7D+)
![= > \frac{ {a}^{2} }{bc} + \frac{ {b}^{2} }{ca } + \frac{ {c}^{2} }{ab} = 3 = > \frac{ {a}^{2} }{bc} + \frac{ {b}^{2} }{ca } + \frac{ {c}^{2} }{ab} = 3](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+%7D%7Bbc%7D+%2B+%5Cfrac%7B+%7Bb%7D%5E%7B2%7D+%7D%7Bca+%7D+%2B+%5Cfrac%7B+%7Bc%7D%5E%7B2%7D+%7D%7Bab%7D+%3D+3)
Proved
That's your answer.
Hope it'll help.. :-)
Then,
Now, dividing both sides by abc, we get
Proved
That's your answer.
Hope it'll help.. :-)
anonymous64:
Comment if any query and please mark as Brainliest
Similar questions